2000
DOI: 10.1093/intimm/12.12.1715
|View full text |Cite
|
Sign up to set email alerts
|

Nasal application of a naturally processed and presented T cell epitope derived from TCR AV11 protects against adjuvant arthritis

Abstract: Reactivity towards TCR peptides plays an important role in the regulation of several experimental autoimmune diseases. In a previous paper, we showed the TCRAV11 usage by an arthritogenic T cell clone isolated from a rat with adjuvant arthritis (AA). Moreover, we identified three immunogenic peptides in AV11: AV11 24-40, 41-55 and 66-80. In the present study, we show that T cells directed towards all three epitopes are part of the immune repertoire. The strongest delayed-type hypersensitivity (DTH) reaction wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…15 In follow-up studies, it was shown that TcR peptides can have the capacity to protect against arthritis in the experimental model upon in vivo nasal administration. 16 Although with the relatively recent revival of interest in T cell regulation the focus of research has been on therapeutic applications of Treg, also the regulatory B cell or the Breg may have the potential for tolerance induction. Although Breg was known to downregulate immune responses by secretion of IL-10 and IL-35, the origin of Bregs had remained a bit unclear.…”
Section: Therapeutic Tolerancementioning
confidence: 99%
“…15 In follow-up studies, it was shown that TcR peptides can have the capacity to protect against arthritis in the experimental model upon in vivo nasal administration. 16 Although with the relatively recent revival of interest in T cell regulation the focus of research has been on therapeutic applications of Treg, also the regulatory B cell or the Breg may have the potential for tolerance induction. Although Breg was known to downregulate immune responses by secretion of IL-10 and IL-35, the origin of Bregs had remained a bit unclear.…”
Section: Therapeutic Tolerancementioning
confidence: 99%